Petrophysics and Exploration Targeting: The Value Proposition. Issue 1 (1st December 2018) - Bourne, Barry; Dentith, Mike; Jumeau, Anthony
Abstract : There is still much that needs to be understood about the physical properties of rocks in mineralised geological environments. This knowledge gap becomes more important as the transition to deeper exploration targets under cover occurs, with an associated greater reliance on geophysical exploration methods. The major challenge associated with understanding petrophysical data is not making the measurement, but rather understanding the results. The interpretation of the data is a cross disciplinary problem. Fundamentally it is necessary to understand the rock mineralogy and geochemistry to put the petrophysics in context with the geophysical results. Several case studies are presented where the petrophysics have determined not only which geophysical techniques to apply but whether a geophysical target has indeed been tested. Drill testing EM plate approximations for nickel sulphide and volcanogenic massive suphide (VHMS) ore deposits can benefit from inductive conductivity measurements on core as it can determine whether an EM conductor has been intersected. Chargeability highs associated with porphyry copper mineralisation is indicative of disseminated pyrite in the propylitic and pyrite +/- chalcopyrite +/-bornite in the potassic alteration zones and higher chargeability does not necessarily mean more copper. In most porphyry systems magnetite is coarse-grained, therefore a world class porphyry deposit should not have dominant remanent effects and the only likely source of remanence features in younger terrains are oxidised mafic intrusions and skarns. Furthermore, porosity and specific types of alteration (argillization) display the strongest correlations with resistivity and can be tied to gold distribution in Carlin Type Deposits.